Local Control and Survival Outcomes After Stereotactic Radiosurgery for Brain Metastases From Gastrointestinal Primaries: An International Multicenter Analysis - Singh, Raj; Bowden, Greg; Mathieu, David; Perlow, Haley K; Palmer, Joshua D; Elhamdani, Shahed; Shepard, Matthew; Liang, Yun; Nabeel, Ahmed M; Reda, Wael A; Tawadros, Sameh R; Abdelkarim, Khaled; et al. (Neurosurgery, 2023)
BACKGROUND: There are limited data regarding outcomes for patients with gastrointestinal (GI) primaries and brain metastases treated with stereotactic radiosurgery (SRS). OBJECTIVE: To examine clinical outcomes after SRS for patients with brain metastases from GI primaries and evaluate potential prognostic factors. METHODS: The International Radiosurgery Research Foundation centers were queried for patients with brain metastases from GI primaries managed with SRS. Primary outcomes were local control (LC) and overall survival (OS). Kaplan-Meier analysis was used for univariate analysis (UVA) of prognostic factors. Factors significant on UVA were evaluated with a Cox multivariate analysis proportional hazards model. Logistic regressions were used to examine correlations with RN. RESULTS: We identified 263 eligible patients with 543 brain metastases. Common primary sites were rectal (31.2%), colon (31.2%), and esophagus (25.5%) with a median age of 61.6 years (range: 37-91.4 years) and a median Karnofsky performance status (KPS) of 90% (range: 40%-100%). One-year and 2-year LC rates were 83.5% (95% CI: 78.9%-87.1%) and 73.0% (95% CI: 66.4%-78.5%), respectively. On UVA, age >65 years ( P = .001), dose <20 Gy ( P = .006) for single-fraction plans, KPS <90% ( P < .001), and planning target volume ≥2cc ( P = .007) were associated with inferior LC. All factors other than dose were significant on multivariate analysis ( P ≤ .002). One-year and 2-year OS rates were 68.0% (95% CI: 61.5%-73.6%) and 31.2% (95% CI: 24.6%-37.9%), respectively. Age > 65 years ( P = .006), KPS <90% ( P = .005), and extracranial metastases ( P = .05) were associated with inferior OS. CONCLUSION: SRS resulted in comparable LC with common primaries. Age and KPS were associated with both LC and OS with planning target volume and extracranial metastases correlating with LC and OS, respectively. These factors should be considered in GI cancer patient selection for SRS.
Keywords: dospělí; Prognosis; senioři nad 80 let; retrospektivní studie; Humans; lidé středního věku; Middle Aged; Aged, 80 and over; Kaplanův-Meierův odhad; prognóza; radiochirurgie; Adult; výsledek terapie; Treatment Outcome; Brain Neoplasms; nádory mozku; lidé; analýza přežití; Aged; Radiosurgery; senioři; Retrospective Studies; Survival Analysis; Kaplan-Meier Estimate